Individual Differences in Convicts Sentenced to Shorter and Longer Prison Terms - Jovanić, Goran; Petrović, Vera; Savić, Ana (Zbornik Instituta za kriminološka i sociološka istraživanja, 2017)
The paper examined individual differences in convicts sentenced to shorter and longer prison terms, as identified in the observational phase of sentence execution. The distinction was made through convict assessment and with regard to the length of prison terms. The sample consisted of the files of the convicts (271), of whom 68 were in the County jail Užice, 53 in the Correctional house Padinska Skela and 150 in the Correctional house Sremska Mitrovica. The short-term sub-sample (less than three years) included convicts from Užice and Padinska Skela (121), while the long-term sub-sample (more than three years) included convicts from Sremska Mitrovica. The data were gathered through the Questionnaire on the risks of convicts sentenced to less than three years, as well as through the Questionnaire on the risks, needs, and capacities of convicts sentenced to more than three years. The reliability of the assessment instruments was acceptable (Cronbach's α = 0,713). The results have revealed the existence of statistically significant differences in numerous characteristics under scrutiny.